2016
DOI: 10.1080/0972060x.2015.1038090
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Antifungal and Antifumonisin Activity ofPinus wallichiana, Pinus monticolaandPinus strobusEssential Oils from Patagonia Argentina

Abstract: The essential oils composition of P. wallichiana P. monticola and P. strobus was determined by GC-FID and GC-MS analysis. Pinus wallichiana was the species with the highest essential oils production with an average yield of 0.97%, followed by P. monticola and P. strobus with 0.58 and 0.50% (v/dry wt).The main compounds with concentration higher than 5.0% were the monoterpene hydrocarbons:α-pinene (14,8 -21%), β-pinene (22,8 -34%), limonene (4,6 -17,8 %) and myrcene (1,6 -12,3%).The essential oils from P. walli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…The leaf extract completely inhibited the mycelial growth of Foc, and this observation was similar to the ones made previously where antifungal efficacy of extracts from distinct species associated with different families of gymnosperms was demonstrated [26] and also the efficacy of botanicals extracted from P. walliachina exhibited prominent antifungal, antibacterial and insecticidal activities [31,37,38,53]. The four fractions of P. walliachina leaf extract recorded significant percent inhibition and zone of inhibition against Foc in the poisoned food and well diffusion assays, respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The leaf extract completely inhibited the mycelial growth of Foc, and this observation was similar to the ones made previously where antifungal efficacy of extracts from distinct species associated with different families of gymnosperms was demonstrated [26] and also the efficacy of botanicals extracted from P. walliachina exhibited prominent antifungal, antibacterial and insecticidal activities [31,37,38,53]. The four fractions of P. walliachina leaf extract recorded significant percent inhibition and zone of inhibition against Foc in the poisoned food and well diffusion assays, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The majority of the research and pharmacognostic studies conducted on P. wallachiana have strongly supported its antioxidant efficacies [ 31 , 32 , 33 , 34 ] and the anticancerous potential of P. wallachiana needle extract [ 35 ]. The antibacterial activity of P. wallachiana essential oil against tested bacterial strains [ 36 ] and antifungal efficacy of its essential oil against Fusarium verticillioides [ 37 ], antimicrobial activity of its hydroalcoholic extracts against tested bacterial strains and fungi [ 38 ], and antibacterial activity against Acinetobacter baumannii [ 29 ] demonstrate its antimicrobial potential. Phytochemical studies have reported the antioxidant activity of P. wallachiana extracts that accounts for the presence of plentiful flavanoids and polyphenols in their phytochemical composition [ 32 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…walliachina exhibited prominent antifungal, antibacterial and insecticidal activities 31,37,38,66 . The four fractions of P. walliachina recorded signi cant percent inhibition and zone of inhibition against Foc in the poisoned food and well diffusion assays respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the research and pharmacognostic studies conducted on P. wallachiana strongly supported its antioxidant e cacies [31][32][33][34] and anticancerous potential of P. wallachiana needle extract 35 . Antibacterial activity of P. wallachiana essential oil against tested bacterial strains 36 and antifungal e cacy of its essential oil against Fusarium verticillioides 37 , antimicrobial activity of its hydroalcoholic extracts against tested bacterial strains and fungi 38 , antibacterial activity against Acinetobacter baumannii 29 put forward its antimicrobial potential. Phytochemical studies reported antioxidant activity of P. wallachiana extracts that accounts for the presence of plentiful avanoids and polyphenols in their phytochemical composition 32,39 .…”
Section: Introductionmentioning
confidence: 99%
“…84 The needle essential oil also showed inhibitory activity against Fusarium verticillioides with minimum inhibitory concentration of 40 ppm exhibiting 25% or less growth than that of the control. 75 It was also reported that the hydromethanolic extract of the needles at concentration of 47.8 mg.ml -1 showed highest inhibitory activity against Pseudomonas aeruginosa and Escherichia coli with a zone of inhibition of 15.66 ± 1.1 mm and 14 ± 0.57 mm respectively. 83 Additionally, the methanolic extract of the needles of the plant showed bactericidal activity against Bacillus subtilis, Agrobacterium tumefaciens, Xanthmonas phaseoli, Erwinia chrysanthemi and Escherichia coli with activities ranging 54% and 81%.…”
Section: Antimicrobial Activitymentioning
confidence: 91%